Patient Satisfaction With Services In The Tpprj Department - Irwan; Wa Ode Sitti Budiaty; Sri Wahyuni (International Journal of Multidisciplinary Learners, 2024)
TPPRJ RSUD Buton Regency has several problems, including long queues due to the lack of speed of officers in serving patients and medical record documents which are sometimes not found when patients seek treatment.. This research aims to identify patient satisfaction in terms of direct evidence (tangibles), reliability, responsiveness, empathy, assurance. The method used is a quantitative analysis method. The population in this study is the number of patient visits in 1 month. The sample used in this research was a sampling technique and used a random sampling technique. Based on the results of the research, it was stated that in the dimension of direct evidence (tangible) there were 37% who said they were very satisfied, 40% who said they were satisfied, 16% who said they were quite satisfied, 4% who said they were dissatisfied, and 1% who said they were very dissatisfied. In the reliability satisfaction dimension, there are 45% very satisfied, 40% satisfied, 22.5% quite satisfied, 5% dissatisfied, 1.3% very dissatisfied. Responsiveness satisfaction: 51.2% very satisfied, 42.5% satisfied, 16.3% quite satisfied, 8.8% dissatisfied, 0% very dissatisfied. empathy satisfaction (empathy) 56.3% very satisfied, 42.5% satisfied, 17.5% quite satisfied, 6.3% dissatisfied, 1.3% very dissatisfied. Guarantee satisfaction (assurance) 66.3% very satisfied, 36.3% satisfied, 12.5% ​​quite satisfied, 5% dissatisfied, 0% very dissatisfied.